Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1177/09567976221083322
|View full text |Cite
|
Sign up to set email alerts
|

Do Positive Psychological Factors Equally Predict Resistance to Upper Respiratory Infections in African and European Americans?

Abstract: Research has consistently shown that positive psychological constructs are linked to better physical health, but few studies have examined the role that race plays in this connection. We explored whether positive self-evaluations were equally protective against upper respiratory infection for 271 African American adults and 700 European American adults in a series of virus-exposure studies. Participants were assessed at baseline for psychological functioning and physical health, quarantined and exposed experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Sixth, the study used a single‐item tool to assess hurt feelings and general health. Although it is acceptable to adopt a single item to assess less complex concepts in a daily setting (e.g., Groen et al, 2022; Wiley et al, 2022), future research may benefit from innovative assessment methods to capture daily functioning while not adding too much response burden to participants. Seventh, the current study did not differentiate between anxious and angry RS (McDonald et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, the study used a single‐item tool to assess hurt feelings and general health. Although it is acceptable to adopt a single item to assess less complex concepts in a daily setting (e.g., Groen et al, 2022; Wiley et al, 2022), future research may benefit from innovative assessment methods to capture daily functioning while not adding too much response burden to participants. Seventh, the current study did not differentiate between anxious and angry RS (McDonald et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, two recent reviews reported that Black and Hispanic individuals experienced higher rates of infection, hospitalization, and COVID-19-related mortality compared to their White peers (Mackey et al, 2021; Mude et al, 2021) and another study found that more racially segregated U.S. counties had higher infection and mortality rates than more integrated counties (Torrats-Espinosa, 2021). Along with racial discrimination and segregation, higher rates of COVID-19 morbidity and mortality among people of color could be due to greater perseveration regarding finances and contracting (and dying from) the virus (Williams et al, 2022). Although further evidence is needed, early evidence shows that, as with other viral infections, susceptibility to and severity of COVID-19 is associated with psychosocial factors.…”
Section: Psychosocial Factors and Covid-19mentioning
confidence: 99%
“…Indeed, even the ability to differentiate and identify distinct affect states is important for tobacco cessation processes [ 32–34 ] as this is a crucial skill for self-regulation [ 35 ]. Not only do distinct positive (e.g., happiness, gratitude, pride) and negative affect states (e.g., anger, sadness, shame) likely have differential impacts on cognition and behavior [ 36 , 37 ], but examining distinct affect among tobacco users who identify as African American is critically important given previous research suggesting that distinct affect states may carry different risk or protective effects for African Americans than European Americans [ 38 ].…”
Section: Introductionmentioning
confidence: 99%